2017
DOI: 10.1186/s12882-017-0624-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of baseline, longitudinal serum high-sensitive C-reactive protein and its change with mortality in peritoneal dialysis patients

Abstract: BackgroundThe prognostic values of baseline, longitudinal high-sensitivity C-reactive protein (hs-CRP) and its change over time on mortality in patients undergoing continuous ambulatory peritoneal dialysis (CAPD) remain uncertain.MethodsWe retrospectively studied 1228 consecutive CAPD patients from 2007 to 2012, and followed up through December 2014. Cox regression models were performed to assess the association of hs-CRP on outcomes using serum hs-CRP levels as: (1) stratified by tertile of baseline or longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The strong power for outcome prediction of this score may be attributed to the combined effects of its components. Both markers, CRP and serum albumin, have been demonstrated to be strongly associated with all-cause and CVD mortality in patients on PD [ 9 11 , 26 , 27 ]. However, ROC analysis revealed that GPS had the higher value than hypoalbuminemia or increased CRP alone (data not shown), which may indicate a reciprocal interaction between these two factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong power for outcome prediction of this score may be attributed to the combined effects of its components. Both markers, CRP and serum albumin, have been demonstrated to be strongly associated with all-cause and CVD mortality in patients on PD [ 9 11 , 26 , 27 ]. However, ROC analysis revealed that GPS had the higher value than hypoalbuminemia or increased CRP alone (data not shown), which may indicate a reciprocal interaction between these two factors.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, systemic inflammation is well recognized for its close relationship to cardiovascular morbidity and mortality [ 8 ]. We and others found that elevated C-reactive protein (CRP) levels, especially its elevated trend over time, could be independently predictive of mortality in PD population [ 9 11 ]. Importantly, inflammation drives the development of malnutrition, which may in turn amplify systemic inflammation responses, leading to a vicious cycle [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most studies involving patients receiving HD, elevated serum UA levels were associated with lower mortality; however, some studies reported either increased or no difference in mortality . On the other hand, in studies involving patients receiving PD, high serum UA levels were not associated with higher mortality, although a few studies showed no association …”
Section: The Meaning Of Elevated Serum Ua In Patients With Eskdmentioning
confidence: 98%
“…The relationship between serum concentrations of UA and mortality was evaluated in 14 studies of patients with ESKD receiving HD and five studies of patients with ESKD receiving PD, summarized in Table . In most studies involving patients receiving HD, elevated serum UA levels were associated with lower mortality; however, some studies reported either increased or no difference in mortality .…”
Section: The Meaning Of Elevated Serum Ua In Patients With Eskdmentioning
confidence: 99%
“…CRP increases glomerular capillary permeability and glomerular mesangial cell hyperplasia through mediating vasoconstriction, embolism, and inflammation. CRP predicts prognosis and stratifies risk in patients with ESRD [ 26 ].…”
Section: Cardiac Biomarkersmentioning
confidence: 99%